The Effects of Combination of Mimic miR-155-5p and Antagonist miR-324-5p Encapsulated Chitosan in Ovarian Cancer SKOV3 - Suardi, Rahma B (Asian Pac J Cancer Prev, 2020)
OBJECTIVE: Ovarian cancer is a malignant tumor that attacks reproductive organs of women. MicroRNA is known to have an involvement in the prognosis of ovarian cancer. One of them is miR-155-5p which is down regulated and miR-324-5p which is up regulated. Chitosan is used as microRNA delivery system. The aims of this study is to find out the effects of combination microRNA encapsulated chitosan in cell line SKOV3. METHODS: Cell line SKOV3 obtained from Stem Cell and Cancer Institute (Kalbe). Mimic miR-155-5p and Antagonist miR-324-5p formulated with chitosan. Total RNA was extracted from nine samples (three as control and six as treatment), and prepared for cDNA synthesis. Expression of RNA and mRNA target was measured using q-PCR Biorad CFX96 C.100 and Gen Ex 7 software. Statistics analysis was measured using SPSS 16.0. RESULTS: The administration of combination microRNA encapsulated with chitosan affect the expression of miR-155-5p and miR-324-5p endogen (P<0.05). The expression of mRNA target HIF1α and GLI1 was down regulated after treatment. The correlation between expression of microRNA and mRNA target was strongly (P<0.05). CONCLUSION: This study successfully presented effects of combination of mimic miR-155-5p and antagonist miR-324-5p encapsulated chitosan which be considered as a potential therapy targets for ovarium cancer.